Perlindungan Hukum Atas Perbedaan Luas Faktual Dengan Surat Ukur Pada Sertifikat Hak Atas Tanah - Hastungkara, Atindriya (Faculty of Law, University of Dr. Soetomo, 2017)
This journal is entitled Legal Protection of Actual Land Differences With Land Rights Certificate. This journal examines the function of the letters in the registration of land rights and how the legal safeguards for the holders of land rights in terms of factual land differences with the letters on the land certificate. The type of research used is normative legal research, which is a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced in accordance with the characteristics of prescriptions of jurisprudence. This normative legal research is a procedure and way of scientific research to find the truth based on the logic of science in terms of normatifnya. So that it can answer the legal issues posed. Further said in doing research law. Approach to the problem of statutory approach (Statute Approach) based on the Act, conceptual approach (Conceptual Approach) based on theories and concepts, and the case approach (Case approach).